Design Guidelines to Connect the Nature in Contemporary Housing with Environmental Sustainability Approach - Nafise i Yari Boroujen; Mehdi Sadvandi; Armin Bahramian (توسعه پایدار شهری)
In recent era, due to rising population and lack of housing, attention to quality of home design has trimmed. While the importance of "Home" in human life is obvious, today houses are just packed boxes without effective relation with its environments. This neglecting occurs while ecological sustainability and balance in addition of human physical and psychological dependence on nature depends on natural green spaces. The issue is that if we can communicate with nature as one of the environmental sustainable development principles in houses architecture. This study seeks to answer this question: How can we design housing in deal with nature and goals of environmental sustainability? Also guidelines are derived various sources which are collected and analyzed by analytical -descriptive method data. The study concludes that by taking steps towards directly connection with nature such as open and closed space, placement of nature in living spaces and on the road of resident’s way, relation with sky and so on, could be design compatible housing that is connected with nature to recreate environmental sustainability.